On the assessment of attitudes towards studying—development and validation of a questionnaire - Brahm, Taiga; Jenert, Tobias (Learning and individual differences : journal of psychology and education)
This research aims to develop and validate an instrument for the assessment of attitudes towards two particular objects: the Higher Education Institution (HEI) and the process of studying. Investigating attitudes towards studying at a HEI in a comprehensive way addresses an important research gap. It connects students' perception of the institution with teaching and learning. To validate the Assessment of Students' Attitudes towards Studying (ASAtS) Questionnaire, data was gathered at three different universities in Switzerland (820 students), Sweden (167) and Germany (133). Overall, the results show the internal consistency of the ASAtS. Its nomological validity is also supported by correlations with other constructs, such as intrinsic motivation and study performance. The ASAtS contributes to the theory on students learning by broadening the scope of research beyond learning in a narrow sense. From a practical point of view, it provides a tool for HE management to monitor students' perception of their HEI.
Keywords: Attitude; Student learning; Higher Education Institution; university; student experience

On the assessment of attitudes towards the study process and the university: Attitudes towards the Study Environment Questionnaire (ASEQ) - Brahm, Taiga; Jenert, Tobias; Euler, Dieter
The purpose of the research was to develop and validate an instrument for the assessment of attitudes towards the study environment in higher education contexts. The questionnaire is designed to measure students' attitudes towards two particular objects: the university (or Higher Education Institution) and the process of studying. Five studies at two different universities were conducted to develop and validate the Attitudes towards the Study Environment Questionnaire (ASEQ). In total, 1640 students filled in the questionnaire. Reliability tests and exploratory factor analysis as well as confirmatory factor analysis showed satisfactory psychometric characteristics of the ASEQ. Each part of the questionnaire is internally consistent and construct validity of the scales is supported by correlations with other constructs as assumed by current theories: Positive attitudinal constructs (normative behavior, autonomy, joy, self-efficacy, and task value) are positively related to intrinsic motivation and the expected study performance while anxiety is negatively related to these constructs. Since attitudes towards the study situation are connected to student engagement and motivation, the study contributes to the theory of student learning by providing a validated instrument to assess attitudes. Thus, the ASEQ can support further research on student performance and development by providing an instrument for the hitherto neglected but nonetheless extremely relevant domain of attitudes. Also, the questionnaire can be used as a diagnostic instrument for higher education faculty and administration to trace students' attitudinal development over time - a factor of prime importance for student socialization during the introductory phase of studying.
Keywords: attitudes; teaching and learning; studying; higher education institution; theory of planned behavior; instrument development

Learning Cultures at Higher Education Institutions: Outlining a wohle-institution approach to teaching and learning - Jenert, Tobias; Gebhardt, Anja
Keywords: earning culture; Lernkultur; whole-institution approach; higher education; Hochschule